The evolution of novel host use is unlikely to be constrained by trade‐offs or a lack of genetic variation - Zachariah Gompert; Joshua P. Jahner; Cynthia F. Scholl; Joseph S. Wilson; Lauren K. Lucas; Victor Soria‐Carrasco; James A. Fordyce; Chris C. Nice; C. Alex Buerkle; Matthew L. Forister (Molecular Ecology, 2015)
The genetic and ecological factors that shape the evolution of animal diets remain poorly understood. For herbivorous insects, the expectation has been that trade‐offs exist, such that adaptation to one host plant reduces performance on other potential hosts. We investigated the genetic architecture of alternative host use by rearing individual Lycaeides melissa butterflies from two wild populations in a crossed design on two hosts (one native and one introduced) and analysing the genetic basis of differences in performance using genomic approaches. Survival during the experiment was highest when butterfly larvae were reared on their natal host plant, consistent with local adaptation. However, cross‐host correlations in performance among families (within populations) were not different from zero. We found that L. melissa populations possess genetic variation for larval performance and variation in performance had a polygenic basis. We documented very few genetic variants with trade‐offs that would inherently constrain diet breadth by preventing the optimization of performance across hosts. Instead, most genetic variants that affected performance on one host had little to no effect on the other host. In total, these results suggest that genetic trade‐offs are not the primary cause of dietary specialization in L. melissa butterflies.